Maternal satisfaction with intrapartum care and associated factors among postpartum women at public hospitals of North Shoa Zone Ethiopia. - Mulualem Silesh; Tesfanesh Lemma (PLoS ONE, 2021)
Background Maternal satisfaction is an essential indicator of the quality and the efficiency of the health care systems. At a time when efforts are being made globally to reduce maternal and neonatal mortality and morbidity, assessing maternal satisfaction is essential. There is a dearth of studies on maternal satisfaction with intrapartum care, particularly in the study area. This study aimed to assess maternal satisfaction with intrapartum care and associated factors among postpartum women at public hospitals of North Shoa Zone Ethiopia. Methods A facility-based cross-sectional study with a systematic random sampling technique was conducted from May1-30/ 2020. Data were entered into EpiData version 4.6 and analyzed using a statistical package for the social sciences version 25. Bivariate and multivariable logistic regression were employed. In multivariable logistic regression analysis, level of statistical significance was declared at variables with p < 0.05 and the strength of the association was measured by an adjusted odds ratio and 95% confidence interval. Result Of the total 394 participants, 111 (28.2%) [95% CI: 23.9, 32.5] of postpartum women were satisfied with the intrapartum care. Place of residence [AOR: 1.934; 95% CI (1.183, 3.162)], planned status of the pregnancy [AOR: 2.245; 95% CI, (1.212, 4.158)], number of antenatal care visit [AOR: 2.389; 95% (1.437, 3.974)] and duration of labour [AOR: 2.463; 95% (1.378, 4.402)] were factors significantly associated with maternal satisfaction with intrapartum care. Conclusion The proportion of maternal satisfaction with intrapartum care was low. Therefore, designing strategies to enhance maternal satisfaction by strengthening adherence to antenatal care visits, provision of family planning to prevent unplanned pregnancy, and strict utilization of partograph to prevent prolonged labour and childbirth-related complications are crucial.